Climate impacts in the Brazilian energy security: analysis of observed events and adaptation options - Vasquez-Arroyo, Eveline; Silva, Fábio da; Santos, Alberto; Cordeiro, Deborah; Marengo, José Antônio; Lucena, André F. P. (Sustainability in Debate, 2021)
Climate change is expected to increase the frequency and intensity of extreme weather events, which can affect energy systems. Thus, this study aims to evaluate impacts of meteorological events on the Brazilian energy system, through an analysis of recent reports. Cases of impacts on hydropower, power transmission and distribution, bioenergy crops and residential cooling demand in recent years are assessed. Finally, the challenges of energy planning in the face of climate change are analyzed and adaptation measures for the energy system are proposed, pointing out possible repercussions on water, food, socio-environmental and climate security.